Reducing radiation exposure during procedures performed in the electrophysiology laboratory. (17th November 2017) - Thibault, Bernard; Macle, Laurent; Mondésert, Blandine; Dubuc, Marc; Shohoudi, Azadeh; Dyrda, Katia; Guerra, Peter G.; Rivard, Léna; Roy, Denis; Talajic, Mario; Khairy, Paul
Abstract: Introduction: Expert societies recently published strong recommendations to reduce the exposure of patients and staff to ionizing radiation (IR) during interventional and electrophysiology (EP) procedures. However, adherence to these guidelines remains difficult and the impact of implementing such recommendations is poorly characterized. Methods and results: We conducted a single‐center cohort study to quantify radiation exposure over time in three EP laboratories at the Montreal Heart Institute during 5, 546 consecutive procedures from 2012 to 2015 by 11 primary operators. Overall, 2, 618 (47.2%) procedures were catheter‐based and 2, 928 (52.8%) were device interventions. Interventions to reduce radiation exposure included educational initiatives to raise awareness (i.e., limiting cine acquisition, patient position, table height), slower frame rate, lower radiation dose per pulse, collimation, and integration with 3‐D mapping systems and/or MediGuide technology. An 85% reduction in IR exposure was observed from 2012 to 2015, with the mean dose‐area‐product (DAP) decreasing from 7.65 ± 0.05 Gy·cm 2 to 1.15 ± 0.04 Gy·cm 2 (P < 0.001). This was true for catheter‐based procedures (mean DAP 16.99 ± 0.08 to 2.00 ± 0.06 Gy·cm 2, P < 0.001) and device interventions (mean DAP 4.18 ± 0.06 to 0.64 ± 0.05 Gy·cm 2, P < 0.001). The median effective dose of IR recorded per quarter by 282 cervical dosimeters on EP staff decreased from 0.57 (IQR 0.18, 1.03) mSv in 2012 to 0.00 (IQR 0.00, 0.19) mSv in 2015, P < 0.001. Conclusion: Enforcing good clinical practices with simple measures and low‐dose fluoroscopy settings are highly effective in reducing IR exposure in the EP lab. These promising results should encourage other EP labs to adopt similar protective measures.